Hacerse un extraño para sí mismo: conocimiento, crueldad y risa en Nietzsche (2020)
In this text I explore the link between bad conscience and the Nietzschean proposal of an experimental philosophy. This link is suggested from the joint reading of two of his works by him: Beyond Good and Evil and The Genealogy of Morality. Specifically, in the second treatise of The Genealogy, bad conscience is defined as cruelty directed at oneself and, in the section Our virtues of Beyond, self-directed cruelty is presented as the foundation of Redlichkeit, virtue that characterizes free spirits. Self-directed cruelty, therefore, is the marrow of this writing. I address this matter in three moments. First, I make a brief characterization of Nietzschean ontology, which serves as a basis for approaching bad conscience and understanding why cruelty is so deeply rooted in humans.